2006
DOI: 10.1093/nar/gkl1059
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of transcriptional dependence and probable target sites for Abf1 and Rap1 in Saccharomyces cerevisiae

Abstract: Abf1 and Rap1 are general regulatory factors (GRFs) that contribute to transcriptional activation of a large number of genes, as well as to replication, silencing and telomere structure in yeast. In spite of their widespread roles in transcription, the scope of their functional targets genome-wide has not been previously determined. Here, we use microarrays to examine the contribution of these essential GRFs to transcription genome-wide, by using ts mutants that dissociate from their binding sites at 37°C. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
107
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 43 publications
12
107
0
Order By: Relevance
“…Although the CDC19 promoter has a Rap1 binding site, little if any dependence on Rap1 was seen for Srb5 recruitment at this promoter, indicating that Mediator recruitment is independent of Rap1 at CDC19. Consistent with this result, expression of CDC19 was not altered at nonpermissive temperature in rap1 ts mutant yeast (37).…”
Section: Mediator Recruitment At Rp Gene Promoters Is Rap1 Dependentsupporting
confidence: 77%
“…Although the CDC19 promoter has a Rap1 binding site, little if any dependence on Rap1 was seen for Srb5 recruitment at this promoter, indicating that Mediator recruitment is independent of Rap1 at CDC19. Consistent with this result, expression of CDC19 was not altered at nonpermissive temperature in rap1 ts mutant yeast (37).…”
Section: Mediator Recruitment At Rp Gene Promoters Is Rap1 Dependentsupporting
confidence: 77%
“…1B), suggesting that they are binding sites for trans-acting regulators. Previous studies in S. cerevisiae (Yarragudi et al 2007;Kaplan et al 2008;Clapier and Cairns 2009) and our own analysis across 12 species (Tsankov et al 2010) have confirmed that such sequences can correspond to binding sites for known general regulatory factors (GRFs), such as Reb1 (Fig. 1B, orange; Badis et al 2008;Zhu et al 2009) and the Rsc3/30 components of the RSC chromatin remodeling complex ( Fig.…”
Section: Identifying Motifs For Trans-acting Chromatin Regulatorssupporting
confidence: 58%
“…Early studies identified the GRFs Abf1 and Rap1 as important in the chromatin structure of the HIS4 promoter (Arndt and Fink 1986;Devlin et al 1991;Yu and Morse 1999;Yarragudi et al 2004), More recently, analysis of genome-wide in vivo nucleosome maps revealed that, in addition to poly(dA:dT), other sequence motifs are associated with nucleosome depletion in vivo, and these correspond to the DNA-binding sites for GRFs such as Abf1, Reb1, and Rap1 (Lee et al 2007b;Yarragudi et al (2007); Badis et al 2008;Kaplan et al 2009;Tsankov et al 2010). These sequences are not nucleosome-depleted in in vitro nucleosome reconstitutions , and this fact has allowed automated determination of GRFs in multiple species by identification of short sequence motifs that are highly nucleosome-depleted in vivo but not in vitro (Tsankov et al 2010).…”
Section: Trans-determinants Of Nucleosome Positioning: General Regulamentioning
confidence: 99%